2005
DOI: 10.1007/s00216-005-3360-8
|View full text |Cite
|
Sign up to set email alerts
|

Mercury depth profiles in river and marine sediments measured by the diffusive gradients in thin films technique with two different specific resins

Abstract: The diffusive gradients in thin films technique (DGT) was used to measure depth profiles of mercury in river and marine sediments in situ to a spatial resolution of 0.5 cm. Agarose gel was used as the diffusive gel in the DGT probes. Two different selective resins-Chelex 100 with iminodiacetic groups and Spheron-Thiol with thiol groups incorporated in the polyacrylamide resin gel-were tested. The different capture efficiencies of the two adsorbents enabled the fractions of mercury bound in different species in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 23 publications
1
23
0
Order By: Relevance
“…42). In a recent study, depth profiles of reactive mercury species were determined in North Sea sediment, and it was found that peak values are reached at the sediment water interface (43). Hence, genes that confer resistance to toxic mercury ions may be much more important for bacteria dwelling in the surface sediment than for bacteria indigenous to the water column.…”
Section: Formation Of Aggregates and Polysaccharide Productionmentioning
confidence: 99%
“…42). In a recent study, depth profiles of reactive mercury species were determined in North Sea sediment, and it was found that peak values are reached at the sediment water interface (43). Hence, genes that confer resistance to toxic mercury ions may be much more important for bacteria dwelling in the surface sediment than for bacteria indigenous to the water column.…”
Section: Formation Of Aggregates and Polysaccharide Productionmentioning
confidence: 99%
“…Hintelmann et al (2002) found that newly deposited Hg is more easily lost through volatilization, suggesting a shallow surface emissions phenomenon. Divis et al (2005) have suggested that Hg emissions from marine and river sediment may be limited to the upper 0 to 4 cm because their data showed large spikes in total and labile Hg in the surface Fe and Mn reduction zone. However, understanding emissions of Hg from varying depths of soils requires further investigation.…”
mentioning
confidence: 99%
“…Samples were analyzed using cold-vapor atomic fluorescence spectroscopy (CVAFS). Three acid solutions were used to test for Hg(II) elution from resin gels: 0.3 M BrCl solution, aqua regia [HNO 3 : HCl (1:3, v/v)], and a mixed acid solution [HNO 3 : H 2 SO 4 (7:3, v/v)]. Inorganic Hg-spiked (5.0 nM) gels were treated in triplicate, and Hg(II) levels in blank samples were also recorded for each acid.…”
Section: Batch Sorption and Elution Testmentioning
confidence: 99%